(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
Induced neutrino charge for Dirac and Majorana type neutrinos has been investigated in this paper. There are some similar and dissimilar features that emerge from the study. That can be summarized as follows. The sign and magnitude of the induced charges depend on their helcities for the neutrino types under consideration. The magnitude can be helicity dependent and dependent on the type of neutrino. However, the induced charge is always anisotropic for both the Dirac type or Majorana type. The anisotropy depends on the angle between the direction of neutrino momentum and the ambient magneticfield.